RESEARCH-AI: Communicating academic honesty: teacher messages and student perceptions about generative AI - Petricini, Tiffany; Zipf, Sarah; Wu, Chuhao (Frontiers in Communication, 2025)
Integrating generative AI (GenAI) in higher education presents both opportunities and challenges, particularly in maintaining academic integrity. This study explores faculty communication strategies when addressing suspected GenAI misuse, analyzing responses through Gallant’s rule-based and integrity-focused frameworks. Data from a survey reveal a dominant reliance on punitive, rule-based approaches, highlighting tensions between students and instructors. While some faculty adopt communicative and educational strategies, fostering trust and collaboration, others exhibit a dismissive stance due to perceived administrative burdens. The findings support the growing research that institutions prioritize educational interventions and support faculty in developing trust-based, proactive strategies for integrating GenAI responsibly.